2004
DOI: 10.1902/jop.2004.75.7.974
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Enhances the Inhibition of Osteoblastic Cell Differentiation Induced by Lipopolysaccharide From Porphyromonas gingivalis

Abstract: These findings suggest that SP inhibits osteoblastic cell differentiation and may be related to bone metabolism in periodontal diseases under conditions of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…Our data also showed that LPS strongly inhibits the expression of Runx2 mRNA in mouse osteoblast MC3T3-E1 cells. These results are consistent with the results reported by previous studies (Azuma et al, 2004;Tomomatsu et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…Our data also showed that LPS strongly inhibits the expression of Runx2 mRNA in mouse osteoblast MC3T3-E1 cells. These results are consistent with the results reported by previous studies (Azuma et al, 2004;Tomomatsu et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…15,16) Much attention was paid to removal of endotoxin from recombinant protein solution after purification. We used a rapid, easy-to-follow procedure and effectively reduced the endotoxin level to less than 0.2 EU for further use in cell experiments, according to the manufacture's instructions for the Endotoxin Removal Kit.…”
Section: Resultsmentioning
confidence: 99%
“…P. gingivalis LPS, lipids, metabolic products and sonicated extracts can inhibit the differentiation and osteogenesis of osteoblasts [5-10], and modulate RANKL (receptor activator of nuclear factor-kappaB ligand) and/or OPG (osteoprotegerin) expression in osteoblasts to indirectly stimulate osteoclastogenesis [11-14]. Recently, our laboratory has established that P. gingivalis can invade osteoblasts and inhibit their maturation and mineralization in vitro [15], and fimbriae play an important role in mediating the initial invasive process [16].…”
Section: Introductionmentioning
confidence: 99%